2012
DOI: 10.1177/109258721201700202
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Activity Involvement and Place Attachment on Volunteer Interpreters’ Satisfaction in Taiwan

Abstract: The purpose of this research was to establish a conceptual model of volunteer interpreters’ satisfaction in Taiwan. The objectives were: (1) to understand Taiwanese volunteer interpreters’ activity involvement, place attachment, and personal satisfaction and (2) to propose a hypothetical structural model representing the association between activity involvement, place attachment, and interpreters’ satisfaction. A total of 378 surveys were collected from volunteer interpreters at six Taiwan national parks and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Suggestions included a broad array of communication/teaching skills, including social/emotional intelligence and pedagogical approaches deemed "best practices" (Bowling, 2013;Ivey & Bixler, 2013;Knapp & Forist, 2014;Powell & Stern, 2013a;Powell et al, 2017;Yamada, 2014); skills and practices associated with how to engage new and diverse audiences (Knapp & Forist, 2014;Powell et al, 2017); skills to identify and apply research to inform the development of innovative interpretive approaches (Powell et al, 2017); increased evaluation skills and literacy so that interpreters and site managers can use evidenced-based decision-making regarding what works and why (aka, adaptive management; Powell et al, 2017); and KSAs associated with using technology, social media, and other distance learning tools (Merson et al, 2016;Powell et al, 2017). Several studies identified specific suggestions for how to provide professional development, including providing opportunities for individual and facilitated reflection (Yamada & Skibins, 2019), training a wider-diversity of staff (anyone that interacts with the public) (Harrison, et al, 2017;Pan et al, 2012;Tschaenn et al, 2014), and conducting regular training needs assessments in response to staff turnover, changing audience characteristics, and the continual evolution of the practice of interpretation (Caplow, 2018;Knapp & Forist, 2014;Powell et al, 2017).…”
Section: Training/professional Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Suggestions included a broad array of communication/teaching skills, including social/emotional intelligence and pedagogical approaches deemed "best practices" (Bowling, 2013;Ivey & Bixler, 2013;Knapp & Forist, 2014;Powell & Stern, 2013a;Powell et al, 2017;Yamada, 2014); skills and practices associated with how to engage new and diverse audiences (Knapp & Forist, 2014;Powell et al, 2017); skills to identify and apply research to inform the development of innovative interpretive approaches (Powell et al, 2017); increased evaluation skills and literacy so that interpreters and site managers can use evidenced-based decision-making regarding what works and why (aka, adaptive management; Powell et al, 2017); and KSAs associated with using technology, social media, and other distance learning tools (Merson et al, 2016;Powell et al, 2017). Several studies identified specific suggestions for how to provide professional development, including providing opportunities for individual and facilitated reflection (Yamada & Skibins, 2019), training a wider-diversity of staff (anyone that interacts with the public) (Harrison, et al, 2017;Pan et al, 2012;Tschaenn et al, 2014), and conducting regular training needs assessments in response to staff turnover, changing audience characteristics, and the continual evolution of the practice of interpretation (Caplow, 2018;Knapp & Forist, 2014;Powell et al, 2017).…”
Section: Training/professional Developmentmentioning
confidence: 99%
“…, Van Winkle (2012),Williams et al (2018) Organizational topics 19Bixler et al (2011);Bowling (2013),Burris (2019),Caplow (2018),Danwandee et al (2015),Ernst (2012),Goodrich and Bixler (2012),Hansen et al (2017),Hvenegaard et al (2016),Ivey and Bixler (2013),Morgan and Kai (2016),Pan et al (2012),Powell et al (2017),Stern et al (2011,Tesdahl (2017),Tschaenn et al (2014),Wolins (2012), Bowling (2013,Burris (2019),Harrison et al (2010), (2017),Ivey and Bixler (2013),Knapp and Forist (2014), Merson et al (2016), Pan et al (2012), Powell et al (2017), Powell and Stern (2013a), Stern et al (2013), Tschaenn et al (2014), Yamada (2014), Yamada and Skibins (2019) Diversity, equity, inclusion and justice 12 Caplow (2018), Clark et al (2011), Hansen et al (2017), Lee et al (2019), Montero et al (2018),Morgan and Hwang, (2014)…”
mentioning
confidence: 99%
“…With regard to the relationship between place attachment and activity satisfaction, the study of Pan et al [23] selected the interpretive volunteers of the National Museum of Natural Science in Taiwan as samples, and found out Activity involvement and place attachment both positively and significantly affect satisfaction. Similar result was got in the study of Lo et al [24].…”
Section: The Relationship Between Activity Involvement Place Attachme...mentioning
confidence: 99%